2014
DOI: 10.1074/jbc.m114.553743
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Reorganization Evoked by Rho-associated kinase- and Protein Kinase C-catalyzed Phosphorylation of Cofilin and Heat Shock Protein 27, Respectively, Contributes to Myogenic Constriction of Rat Cerebral Arteries

Abstract: Background:The myogenic response of cerebral arteries to intravascular pressure regulates blood flow to the brain. Results: Pressurization reduced smooth muscle G-actin and increased phospho-cofilin and -HSP27 content by a mechanism blocked by ROK or PKC inhibitors. Conclusion: ROK-and PKC-mediated control of cofilin and HSP27 contributes to actin polymerization in myogenic constriction. Significance: Knowledge of cytoskeletal dynamics is crucial for understanding myogenic control of cerebral arterial diameter. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 100 publications
(130 reference statements)
2
59
0
Order By: Relevance
“…Although our studies were performed in vessels from skeletal muscle, it has been demonstrated in rat middle cerebral arteries that 5-HT increases the phosphorylation state of cofilin and reduces the concentration of G-actin, indicating that 5-HT-induced remodeling of the actin cytoskeleton also occurs in the cerebral circulation (36), where localized vasoconstriction or vasospasm following subarachnoid hemorrhage or hemorrhagic stroke hinders blood flow re-establishment (8,12,39). Moreover, in a rat model of subarachnoid hemorrhage, inward remodeling of middle cerebral arteries, following exposure to hemolyzed blood, is blocked by inhibition of transglutaminases (17).…”
Section: ϫ4mentioning
confidence: 99%
“…Although our studies were performed in vessels from skeletal muscle, it has been demonstrated in rat middle cerebral arteries that 5-HT increases the phosphorylation state of cofilin and reduces the concentration of G-actin, indicating that 5-HT-induced remodeling of the actin cytoskeleton also occurs in the cerebral circulation (36), where localized vasoconstriction or vasospasm following subarachnoid hemorrhage or hemorrhagic stroke hinders blood flow re-establishment (8,12,39). Moreover, in a rat model of subarachnoid hemorrhage, inward remodeling of middle cerebral arteries, following exposure to hemolyzed blood, is blocked by inhibition of transglutaminases (17).…”
Section: ϫ4mentioning
confidence: 99%
“…Of note, of 6 studies focusing especially on VSM, 5 reported increased cofilin phosphorylation in response to contractile stimulation. 39,[44][45][46][47] If one can conclude that vasodilation should lead to opposite changes, the majority of these studies are consistent with cofilin dephosphorylation being a relevant factor in controlling cytoskeletal changes, which ultimately lead to vasodilation. However, one vascular study also reported decreased phosphorylation with contraction.…”
Section: Discussionmentioning
confidence: 57%
“…Impaired actin polymerization indeed hampers contractile processes, despite unaltered MLC 20 phosphorylation levels. 38,39 Using confocal microscopy and differential ultracentrifugation, we were able to detect significant increases in the G-actin fraction after AMPK activation for 35 minutes. This effect of PT1 was indeed AMPK mediated because pretreatment with siRNA completely abolished the increase in G-actin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The nonmuscle actin cytoskeleton and FAs to which it is attached have been shown to display plasticity in the presence of agonists26 and biomechanical stimuli27, 28 by exhibiting stimulus‐induced increases in actin polymerization and endosomal‐dependent remodeling of a subset of FA proteins 29. Plasticity of the cortical cytoskeleton of VSMCs may contribute to the function of the healthy, compliant proximal aorta, acting as a tunable “shock absorber” that adapts in order to limit transmission of excessive pulsatile energy into the delicate downstream microvessels.…”
Section: Introductionmentioning
confidence: 99%